2006
DOI: 10.1016/j.bbabio.2006.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA involvement in human longevity

Abstract: The main message of this review can be summarized as follows: aging and longevity, as complex traits having a significant genetic component, likely depend on a number of nuclear gene variants interacting with mtDNA variability both inherited and somatic. We reviewed the data available in the literature with particular attention to human longevity, and argued that what we hypothesize for aging and longevity could have a more general relevance and be extended to other age-related complex traits such as Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 105 publications
1
45
0
Order By: Relevance
“…We regard this result as very important, particularly in relation to the many results recently obtained in genetics. All the data collected in this and other studies suggest that, as well as a variety of nuclear DNA polymorphisms (Di Bona et al 2009;Gravina et al 2009;Invidia et al 2010;Lescai, Marchegiani, and Franceschi 2009;Salvioli et al 2006;Testa et al 2009), maternally inherited mitochondrial DNA variants (Capri et al 2008;Raule et al 2007;Rose et al 2007;Rose et al 2010;Santoro et al 2006) contribute substantially to human longevity too.…”
Section: Some Preliminary Resultsmentioning
confidence: 56%
“…We regard this result as very important, particularly in relation to the many results recently obtained in genetics. All the data collected in this and other studies suggest that, as well as a variety of nuclear DNA polymorphisms (Di Bona et al 2009;Gravina et al 2009;Invidia et al 2010;Lescai, Marchegiani, and Franceschi 2009;Salvioli et al 2006;Testa et al 2009), maternally inherited mitochondrial DNA variants (Capri et al 2008;Raule et al 2007;Rose et al 2007;Rose et al 2010;Santoro et al 2006) contribute substantially to human longevity too.…”
Section: Some Preliminary Resultsmentioning
confidence: 56%
“…Mitochondrial haplogroups can modulate mitochondrial metabolism (leading to mild differences in OXPHOS activity), and they could also affect the cross talk that exists between nuclear and mitochondrial genomes (65,66). Research on mouse cell lines with homogeneous nuclear genome and different mitochondrial haplogroups showed an effect of mitochondrial haplogroups on cell respiration and defenses against ROS (54).…”
Section: Mitochondrial Dna and Elite Athletic Statusmentioning
confidence: 99%
“…They can influence spermatozoa motility (52,65) or the development of mitochondrial disorders (29). Mitochondrial haplogroups could also have an effect on human longevity, at least in some ethnic/geographical cohorts (18,38,56,63,64,66,75,83).…”
Section: Mitochondrial Dna and Elite Athletic Statusmentioning
confidence: 99%
“…[86,87]. It has been suggested that mitochondrial haplogroups have the potential to modulate mitochondrial metabolism (leading to mild differences in OXPHOS activity), and hence may affect the training response [88].…”
Section: Mitochondrial Haplogroups and Their Association With Trainabmentioning
confidence: 99%